An investigation of microclimatic influence of a forest edge micro-climate on agricultural production - Manyanya, T.C; Kori, Edmore (European Journal of Sustainable Development, 2014)
Human social structures and their development significantly depend on the maintenance and conservation of the environmental resources they require for survival. Forests have been known to be sources of raw materials and resources for sectors of human livelihoods such as healthcare, household uses and agriculture, among others. Understanding the influence of forests on agriculture not only improves the agricultural practices but also enhances eco-friendly development and sustainability. This paper investigates the relationship between forest edge microclimates and agricultural cropproduction. The study adopted a Bio-geographical approach buttressed on the Mono-Climax Theory (MCT) and Holdridge’s Deterministic Approach (HAD). Data for this study comprised of agricultural cropproduction for 2012 collected from farmers along the edge of Thathe Forest in Limpopo, South Africa,in all the four cardinal directions. Vegetation density and composition from the forest edge in all the four cardinal directions was collected through quadrats. Linear regression between agricultural productivity, as the dependent variable, and vegetation composition and density, as independent variables, was employed to determine the relationship. Results reveal that agricultural crop production, vegetation density decrease andcomposition change as one moves from the forest edge. We conclude that Thathe forest creates an important micro-climate for agriculture. As such the forest should be conserved for sustainable agricultural production and development. Key terms: Micro-climate,Bio-geographical, sustainability, vegetation, agriculture.